2007
DOI: 10.1016/j.bbrc.2007.05.177
|View full text |Cite
|
Sign up to set email alerts
|

An outwardly rectifying anionic background current in atrial myocytes from the human heart

Abstract: This report describes a hitherto unreported anionic background current from human atrial cardiomyocytes. Under whole-cell patch-clamp with anion-selective conditions, an outwardly rectifying anion current (IANION) was observed, which was larger with iodide than nitrate, and with nitrate than chloride as charge carrier. In contrast with a previously identified background anionic current from small mammal cardiomyocytes, IANION was not augmented by the pyrethroid tefluthrin (10 μM); neither was it inhibited by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…S16) reported from human atrial cardiomyocytes (54). We added two recently characterized atrial-predominant currents (I K2P (121) and I KCa (122)), updated model formulations of I Kr (123), I Ks (37), I K1 (49, 124), I ClB (125), and I na (49), and included the late Na + current component I NaL (44). Detailed descriptions of updates made to the atrial model of electrophysiology and Ca 2+ is given in SI Appendix, Supplementary Methods .…”
Section: Methodsmentioning
confidence: 99%
“…S16) reported from human atrial cardiomyocytes (54). We added two recently characterized atrial-predominant currents (I K2P (121) and I KCa (122)), updated model formulations of I Kr (123), I Ks (37), I K1 (49, 124), I ClB (125), and I na (49), and included the late Na + current component I NaL (44). Detailed descriptions of updates made to the atrial model of electrophysiology and Ca 2+ is given in SI Appendix, Supplementary Methods .…”
Section: Methodsmentioning
confidence: 99%
“…Studies of human cardiac myocytes identified an additional background anion current, termed I ANION , that differed in ionic selectivity from I AB in the guinea pig heart and also was not activated by tefluthrin (Li et al 2007). The molecular basis of this current and its relationship to I AB and other chloride currents in cardiac tissue remains to be clarified.…”
Section: Actions On Chloride Channelsmentioning
confidence: 99%